The Impact of Russia -Ukraine War on The U.S. Stock Market–Based on Event Study Methodology - Liu, Hongyu; Pei, Zihang; Wei, Wenjie (BCP Business & Management, 2022)
Since Russia is important energy exporter in the world, the conflict between Russia and Ukraine became a world focus nowadays. According to former researchers’ works, we choose the event analysis method to gain an insight into the typical effect on energy sector caused by this conflict and give two hypotheses. Firstly, we propose that the event would have a negative shock on the energy career showed with volatilities of index. And then we present that the fungibility of energy industry remains the stability of returns of index and stocks. By extracting returns and volatilities of SP500 index and returns of the Great consumption index of China from Wind database, also filtrating the famous energy sector U.S. stocks based on the list in the Eastern Wealth, we prove the assumptions with examining the significance of statistics. Using the event analysis method to examine the difference of before and after the event, we get the results which indicate the significances of volatilities of SP500 index. But the returns of SP500 index, the Great consumption index of China, and U.S. stocks do not show the significance differences. Contents above prove two assumptions we mentioned before. It is honorable for us that this research might be practical to offer advice and give a little guidance for market investors.